Decreased rates of methionine synthesis by methylene tetrahydrofolate reductase-deficient fibroblasts and lymphoblasts. - Boss, G R (1981)
Methionine synthesis from homocysteine was measured in intact human fibroblasts and lymphoblasts using a [14C]formate label. Seven fibroblast lines and two lymphoblast lines derived from patients with 5,10-methylene tetrahydrofolate reductase deficiency had rates of methionine synthesis that were from 4 to 43% of normal. When the patients were divided by clinical status into mildly (two patients), moderately (two patients), and severely (three patients) affected, methionine biosynthesis expressed as a percent of control values was 43 and 33%, 11 and 10%, and 7, 6, and 4%, respectively, in fibroblasts. Similar data for the two lymphoblast lines were 36 and 26% for a mildly and moderately affected patient, respectively. These data are to be contrasted with the measurement of residual enzyme activity in cell extracts which agrees less precisely with the clinical status of the patients. In the presence of normal methionine synthetase activity, the rate of synthesis of methionine from homocysteine is a function of the activity of the enzyme 5,10-methylene tetrahydrofolate reductase, and measurement of the methionine biosynthetic capacity of cells deficient in this enzyme accurately reflects the clinical status of the patient from whom the cells were derived.